Attitude Determinants in Proposed Goods and Services Tax among Manufacturing Companies in Malaysia - Zainol Bidin; Munusamy Marimuthu (International Review of Management and Marketing, 2016)
Malaysian Government wanted to replace the Sales and Service Tax with Goods and Services Tax (GST). The government would only introduce once everyone understand and familiar with the tax. This study is aimed to identify the determinants of attitudes towards the proposed GST among managers of manufacturing companies in Malaysia. Four (4) variables were used to measure determinants of attitude comprising awareness, understanding, preparedness and probable area of difficulties. A survey was carried out to acquire the data from 1,500 managers of manufacturing companies throughout Malaysia via questionnaire. Only 210 responded where nine (9) questionnaires were unusable giving a 13.4% (201) response rate. Data were analyzed using descriptive statistics on the demographic variables and five (5) constructs. Test of reliability and validity were also done on the five (5) variables. All the items in the five (5) constructs have mean score of above 3.00. Both the cronbach alpha value and KMO value have more than 0.70 for all the five (5) constructs. The study has a compatibility matching of 41.8% variance (R square) and significant (P<0.00) which shows that the determinants in attitude towards the proposed GST can be explained by the four (4) variables; awareness, understanding, preparedness and probable area of difficulties variables. The findings also found that that the four (4) variables are significant and positively related to attitude towards the proposed GST. Thus this study provides important and valuable inputs for the Government to implement strategic plan to enhance GST knowledge among managers of manufacturing companies in Malaysia in so that GST can be introduced without obstacles. Keywords: Attitude, Awareness, Understanding, Preparedness, Probable Area of Difficulties JEL Classifications: H20, H25